2022
DOI: 10.7717/peerj.14039
|View full text |Cite
|
Sign up to set email alerts
|

Simulating physiological flexibility in the acute glucocorticoid response to stressors reveals limitations of current empirical approaches

Abstract: Wild animals often experience unpredictable challenges that demand rapid and flexible responses. The glucocorticoid mediated stress response is one of the major systems that allows vertebrates to rapidly adjust their physiology and behavior. Given its role in responding to challenges, evolutionary physiologists have focused on the consequences of between-individual and, more recently, within-individual variation in the acute glucocorticoid response. However, empirical studies of physiological flexibility are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Given these challenges, progress will require a combination of traditional field-based approaches, consideration of different experimental design and sampling schemes [19] and collaboration between empiricists and theoreticians to generate novel hypotheses, confirm empirical findings and guide empirical work towards collecting critical missing data. For example, experimental treatments that combine samples from multiple individuals can describe group-level differences in hormonal reaction norms that circumvent the limitations of repeated sampling within individuals [30,118].…”
Section: Future Directions and Open Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given these challenges, progress will require a combination of traditional field-based approaches, consideration of different experimental design and sampling schemes [19] and collaboration between empiricists and theoreticians to generate novel hypotheses, confirm empirical findings and guide empirical work towards collecting critical missing data. For example, experimental treatments that combine samples from multiple individuals can describe group-level differences in hormonal reaction norms that circumvent the limitations of repeated sampling within individuals [30,118].…”
Section: Future Directions and Open Questionsmentioning
confidence: 99%
“…Field-based observation and capture will remain a central focus of endocrine flexibility and recent studies have demonstrated that these approaches can be successful despite the data hungry nature of reaction norm models [26]; in the future, it may be possible to repeatedly measure plasma hormone levels with bio-loggers, which would be a breakthrough for studies of endocrine flexibility. At present, excellent models for study design and necessary sample sizes can be borrowed from the behavioural reaction norm literature [52,117] and several recent papers detail particular considerations for physiological traits like hormones [18,19,51].…”
Section: Future Directions and Open Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Field-based observation and capture will remain a central focus of endocrine flexibility and recent studies have demonstrated that these approaches can be successful despite the data hungry nature of reaction norm models [26]; in the future, it may be possible to repeatedly measure plasma hormone levels with bio-loggers, which would be a breakthrough for studies of endocrine flexibility. At present, excellent models for study design and necessary sample sizes can be borrowed from the behavioral reaction norm literature [52,117] and several recent papers detail particular considerations for physiological traits like hormones [18,19,51].…”
Section: Future Directions and Open Questionsmentioning
confidence: 99%
“…Unfortunately, most physiological traits are not preserved in traditional specimens or reported by community scientists and few resources exist to evaluate whether there have been similar long-term changes in these response systems. Recent studies have begun to shed light on the macroevolutionary patterns of hormone levels in relation to climate [e.g., 17], but collecting these data is challenging and it is even more difficult to measure endocrine flexibility because cross-sectional studies or measurements under a single set of conditions may not capture critical variation in flexibility [18][19][20].…”
Section: Introductionmentioning
confidence: 99%